Identificação molecular de espécies de Characidium (Characiformes: Crenuchidae) de diferentes bacias hidrográficas neotropicais - Costa, Rita Baldini da (2022)
Characidium is the largest genus, in number of valid species (83), of the Crenuchidae. It is widely distributed in the Neotropical region, living in streams, lakes and lowland swamps. It is a cryptic genus in systematics due to its complex morphological delimitation. Therefore, this study aimed to use the DNA barcoding technique to identify the species of Characidium, seeking subsidies to understand its tributary diversity from the Upper Paraguay, Madeira, Tapajós and Xingu basins. The dataset is composed of 124 sequences of the COI gene of Characidium, of which 106 were collected in the present study in the Upper Paraguay (70), Madeira (9), Tapajós (15) and Xingu (12) basins. A priori, they were identified based on morphological characters such as: C. zebra (32), C. aff. steindachneri (4), C. xavante (16), C. laterale (10) and 7 probable new species Characidium sp.1 (11), Characidium sp.2 (4), Characidium sp.3 (8), Characidium sp.4 (2), Characidium sp.5 (4), Characidium sp.6 (9) and Characidium sp.7 (2). To compose the dataset, nine sequences available in the BOLD Systems database were added, namely: C. zebra (9), C. marshi (2), C. lagosantensis (1), C. gomesi (2), C fasciatum (2), C. rachovii (1), C. alopioi (1), C. xanthopterum (1), C. schubarti (1), C. oiticicai (1) and C. phoxocephalum (1). The results revealed a 612 bases pair (bp) sequence of the mitochondrial Cytochrome C oxidase subunit 1 (COI) gene fragment. The OT species delimitation analyzes indicated the presence of 20 Molecular Operational Taxonomic Units (MOTUs) while bPTP identified 25 MOTUs. On the other hand, ASAP and GMYC revealed 23 MOTUs, which were considered in this study as consensus MOTUS, of which two contain C. gomesi and six distinct MOTUs are composed of C. zebra. In the present work, it is evident that the species identified as C. zebra (Madeira and Upper Paraguay) form a distinct group from the species of C. zebra deposited in BOLD. As described in the literature C. zebra is considered a species complex. Our data corroborate that the species currently described as C. zebra lacks more detailed studies, integrating molecular and morphological data for a better understanding of its taxonomic status. The boundary analyzes also revealed three possible sympatric species: C. zebra, C. aff. steindachneri and Characidium sp.1 in the Aricá-açu river (Upper Paraguay). In the Santana River (Upper Paraguay) the presence of C. zebra and Characidium sp.4 was verified, also in sympatry. Finally, the present work reveals that the Characidium diversity is underestimated for the sampled region, indicating the possible presence of at least four new species for the region.